R, Hubungan Hubungan Antara ASI Eksklusif, Berat Badan Lahir Rendah Dan Asupan Makanan Dengan Kejadian Stunting Pada Anak Usia 24-59 Bulan - Novia Wahyu Rasthania Irawan; Andiani; Suryani Mansyur; Diah Merdekawati Surasno (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
This type of research is quantitative analytic with a case-control approach. This study aimed to determine the relationship between exclusive breastfeeding, low birth weight, and food intake with the incidence of stunting in children aged 24-59 months in the Jambula Care Health Centre Working Area. This research was conducted in the working area of ​​Jambula Health Center with a sample of 60 children aged 24-59 months, consisting of 30 children aged 24 - 59 months (Case) and 30 children aged 24 -59 months (Control). The study's dependent variable was the incidence of stunting in children aged 24-59 months. In contrast, the independent variables were the history of exclusive breastfeeding, the history of LBW, and food intake. The results showed a significant relationship between a history of exclusive breastfeeding (p = 0.000), energy intake (p = 0.000), and protein intake (p = 0.045) with the incidence of stunting in children aged 24-59 months in the Jambula Health Center Work Area, while the history of LBW (p = 0. 492) does not have a relationship with the incidence of stunting in children aged 24-59 months in the Jambula Health Center Work Area. It is recommended to mothers and the community to always pay attention to the nutritional intake consumed by children, including exclusive breastfeeding and various nutritious foods. In addition, the active role of Health Workers in Health Service Facilities needs to be increased to prevent and overcome stunting problems in the regions.